Pengaruh Faktor Organisasional, dan Non Organisasional terhadap Komitmen Organisasi dengan Disiplin Kerja sebagai Variabel Intervening pada Driver Gojek Cabang Makassar - Azizah, Nurul; Gani, Nuraeni; wahyudiyud (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
This research aims to find out the influence of organizational and non-organizational factors on organizational commitment with work discipline as an intervening variable. This research uses quantitative research with an associative approach. The data analysis method used in this research is path analysis. This research was conducted at PT. Gojek Indonesia Cab. Makassar by distributing questionnaires to 130 respondents. Testing the research hypothesis used model testing techniques (path analysis) with the SPSS (Statistical Package for the Social Sciences) version 26 application tool. The results of this study found that organizational and non-organizational factors had a positive and significant effect on organizational commitment, organizational factors had a positive effect and significant on organizational commitment partially, non-organizational factors have a positive and insignificant effect on organizational commitment partially, and finally work discipline has a positive and significant effect on organizational commitment partially.